33 Optimising patient experience within the achd outreach network: a questionnaire based study. (2nd February 2018) - Ooues, G; Clift, P; Bowater, S; Arif, S; Epstein, A; Prasad, N; Adamson, D; Cummings, M; Spencer, C; Woodmansey, P; Ingram, T; Morley-Davies, A; et al.
Abstract : Purpose: The NHS England Congenital Heart Disease standards review is based on a network model to deliver high quality, safe and effective services as locally as possible. We developed a Patient Questionnaire across our Adult Congenital Heart Disease (ACHD) West Midlands network to measure patient experience, satisfaction and to improve services across the network. Methods: Patient questionnaires were distributed to patients in all 8 Outreach and the Level 1 ACHD Centre (University Hospital Birmingham). Data was analysed including patients' replies on travel to outpatient clinic, satisfaction on location and timing of their appointment, review by ACHD Specialist Nurse and tests performed, information on their condition and leaflets provided and patients' demographics. Results: 130 questionnaires were returned. The majority of patients (67%, n=87) travelled to their appointment with their own car, either alone (36%, n=46) or with a member of their family (44%, n=56). Most patients (93%, n=120) travelled less than one hour to hospital and less than 20 miles (86%, n=99). Patients attending Level 1 Centre appointments travelled a longer distance (mean 29.6±44 miles) compared to the Outreach Centres (mean 9.9±2.8 miles). Almost all patients found the appointment time and location convenient for them (91%, n=117% and 95%, n=121), and were given enough information regarding their condition (85%, n=98). Conclusion: With the development of ACHD Network Outreach clinics to facilitate services and appointments closer to patients' homes, travel times are reduced and high patient satisfaction is maintained.